2014
DOI: 10.1038/ki.2014.84
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of ErbB4 accelerates polycystic kidney disease progression in cpk mice

Abstract: ErbB4 is highly expressed in the cystic kidneys with polycystic kidney diseases. To investigate its potential role in cystogenesis, cpk mice carrying a heart-rescued ErbB4 deletion were generated. Accelerated cyst progression and renal function deterioration were noted as early as 10 days postnatally in cpk mice with ErbB4 deletion compared to cpk mice, as indicated by increased cystic index, higher kidney weight to body weight ratios and elevated BUN levels. No apparent defects in renal development were noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Veikkolainen et al demonstrated that ErbB4 participates in the proliferation and polarization of renal epithelial cells and in the formation of ducts during kidney development [34]. In addition, a recent study reported that ErbB4 knockout accelerated the progression of polycystic kidney disease [35]. We have confirmed the direct regulation of ErbB4 by miR-146b through dual-luciferase reporter assays.…”
Section: Discussionsupporting
confidence: 76%
“…Veikkolainen et al demonstrated that ErbB4 participates in the proliferation and polarization of renal epithelial cells and in the formation of ducts during kidney development [34]. In addition, a recent study reported that ErbB4 knockout accelerated the progression of polycystic kidney disease [35]. We have confirmed the direct regulation of ErbB4 by miR-146b through dual-luciferase reporter assays.…”
Section: Discussionsupporting
confidence: 76%
“…It shows minimal expression in the adult kidney. Although ErbB4 is highly up-regulated in the kidneys with polycystic kidney disease, its genetic deletion protected animals from polycystic kidney disease, suggesting a complex and unclear role for ErbB4 in development and disease pathogenesis (74). Here, our results show that ErbB4 is up-regulated in diabetic glomeruli and in podocytes, suggesting that it plays a role in diabetic podocyte injury.…”
Section: Mir-146 In Podocytes and Diabetic Injurymentioning
confidence: 55%
“…Recently, experimental studies have shown that activation of this EGF receptor by binding with the ligands EGF or TGF-a results in cyst formation in vitro (8) and in vivo (9). Inhibition of EGF receptor tyrosine kinase activity blocked tubular cyst formation in an in vitro system (14), blockade of EGF receptor resulted in attenuation of cystic disease in animal models (15,16), whereas ErbB4 knockout mice showed an accelerated cyst progression and renal function deterioration (17). Together, these experimental studies provide compelling evidence that the EGF receptor pathway is involved with disease progression in ADPKD.…”
Section: Discussionmentioning
confidence: 87%